The State of Public Finances-Outlook and Medium-Term Policies After the 2008 Crisis. (Policy Papers; Policy Paper ;, 2009)
This paper quantifies the fiscal implications of the crisis, assesses the status of fiscal balances after the shock, and discusses the strategy to ensure fiscal solvency. The focus is primarily on advanced and emerging economies, complementing the Board paper on the effect of the crisis on low-income countries. While, for practical purposes, some of the empirical evidence presented refers only to the G-20, information is provided also for other countries, and the analysis also applies to them. A Companion Paper provides supporting material. As a general caveat, the estimates presented are subject to a significant degree of uncertainty, and developments should be closely monitored as new information becomes available.